In situ biomethanation: Inoculum origin influences acetate consumption rate during hydrogen addition. (June 2021) - Vechi, Nathalia Thygesen; Agneessens, Laura Mia; Feilberg, Anders; Ottosen, Lars Ditlev Mørck; Kofoed, Michael Vedel Wegener
Abstract: Biological conversion of carbon dioxide (CO2 ) to methane (CH4 ) through the exogenous addition of hydrogen (H2 ) represent a promising biotechnology for biogas upgrading and energy conversion through the process of H2 -mediated biomethanation. Acetate accumulation has however been observed during H2 addition, which may deteriorate process stability. Using 13 C-isotope techniques, we found that acetate consumption declined by 84% upon H2 addition in digestate from lab-scale digesters treating agricultural waste products (AD-Manure) but did not decline in digestate based on wastewater treatment sludge (AD-WWT). Dominance of different acetoclastic methanogens, along with the fact that the H2 -sensitive process of syntrophic acetate oxidation (SAO) was responsible for converting 27% of the acetate in AD-Manure and only 4% in AD-WWT, could explain the different response of AD-Manure and AD-WWT. Our results improve the understanding of acetate consumption rates during H2 addition in reactors treating different organic feedstock, and how these are suited for H2 -mediated biomethanation. Graphical abstract: Unlabelled Image Highlights: Stable 13 C isotope experiments to identify carbon fluxes during H2 addition. H2 addition decreased acetate consumption rate in AD-Manure but not AD-WWT. SAO and acetoclastic methanogens determined the effect of H2 on acetate consumption. Minor contribution of homoacetogenesis to H2 uptake